Interdisciplinary treatment in office bleaching for discoloration teeth with altered passive eruption: a case report: Perawatan interdisiplin in office bleaching untuk perubahan warna gigi dengan altered passive eruption: laporan kasus - Juni Jekti Nugroho; Ni Putu Sartika Sukma Putri (Makassar Dental Journal, 2022)
Objective: This case report aims to present in office bleaching treatment to restore the aesthetics of the teeth in a minimally in-vasive manner on a 35-year-oldwoman who had discolored teeth. The patient has a habit of consuming tea 2 times a day. Method: Tooth discoloration is treated by in office bleaching treatment using 40% hydrogen peroxide. In addition to discoloration, the teeth also experienced altered passive eruption thus a crown lengthening treatment was performed on teeth 13 to 23 by a perio-dontist. Two weeks later, in office bleaching treatment was performed. Result: There was an increase of 4 gradessubsequent to in office bleaching treatment from shade guide number 7 (D2) to number 3 (W3) with cervical improvement. Conclusion: In office bleaching is effective in treating tooth discoloration and is able to provide satisfactory results.